2022
DOI: 10.3390/ijms232314629
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Performances in Self-Assembled Hierarchical Nanosegregated Chiral Intermediate Phases Composed of Two Different Achiral Bent-Core Molecules

Abstract: In this paper, chiral intermediate phases composed of two achiral molecules are fabricated by utilizing nanophase separation and molecular hierarchical self-organization. An achiral bent-core guest molecule, exhibiting a calamitic nematic and a dark conglomerate phase according to the temperature, is mixed with another achiral bent-core host molecule possessing a helical nanofilament to separate the phases between them. Two nanosegregated phases are identified, and considerable chiroptical changes, such as cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In M1, the CD intensity increased at approximately 400 nm. This is a typical feature of the nanoseparated phase between the HNF phase and the rod-like nematogen, and it has been reported in numerous binary mixture systems composed of the HNF phase and a rod-like nematogen [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In contrast, the CD peak disappeared in M2.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In M1, the CD intensity increased at approximately 400 nm. This is a typical feature of the nanoseparated phase between the HNF phase and the rod-like nematogen, and it has been reported in numerous binary mixture systems composed of the HNF phase and a rod-like nematogen [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In contrast, the CD peak disappeared in M2.…”
Section: Resultsmentioning
confidence: 73%
“…The XRD profile of the DC showed broader peaks than that of the typical HNF. Although DCs in numerous BC molecules show featureless XRD patterns, an XRD pattern similar to that of BC-B has been observed for certain BC molecules [ 23 , 30 ]. The XRD pattern of M2 was similar to that of the nematogen, which indicated that the aggregates of the DC were diluted by mixing the nematogen with the DC.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Achiral bent-core (BC) molecules are known for their spontaneous chiral resolution on a microscopic scale. , An example of a chirally segregated phase is the B4 phase, typically the lowest-temperature phase of BC molecules, comprising helical nanofilament (HNF) superstructures that spontaneously self-assemble. CPLE has been successfully induced in a mixed system consisting of a BC molecule (host), a calamitic nematic liquid crystal (NLC) molecule (guest), and a small amount (1–2 wt %) of luminescent dye. , Combining BC and NLC molecules allows phase separation between the semicrystalline HNF and NLC because NLCs are expelled by the HNFs.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral materials have attracted considerable attention owing to their wide range of potential applications in electronics, optics, and spintronics. These applications are made possible by the unique and intriguing physical and optical properties of chiral materials, such as circular dichroism (CD), circularly polarized light emission (CPLE), nonlinear optical effects, and ferroelectricity. Among common optoelectronic materials, halide perovskites possess favorable physicochemical properties, such as structural flexibility, a wide tunable band gap, high optical absorbance, high dielectric permittivity, large charge-carrier diffusion lengths, and strong spin–orbit coupling. Consequently, halide perovskites are promising optoelectronic materials for various applications, including solar cells, , light-emitting diodes, photonic lasers, , and photodetectors. , However, conventional halide perovskites lack chirality at the molecular level and do not exhibit CD and CPLE behavior, making them unsuitable for chirality-related applications. Therefore, the introduction of chirality into nonchiral perovskites can address this limitation and expand their potential applications.…”
mentioning
confidence: 99%